Pengaruh Penerapan Pembelajaran Kooperatif Tipe Mind Mapping terhadap Hasil Belajar Siswa Kelas V pada Pembelajaran Tematik - Rianita, Riandini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to analyze the effect of the application of a mind mapping type cooperative learning model on students' cognitive learning outcomes n thematic learning of grade V of State Elementary School 84 Sngkawang. The method used was an experiment with a quas experimental design type of nonequivalent control group desgn. The population was all students from two classes totaling 45 students. The samples of this study were VA class students totaling 23 students and VB class students totaling 22 students. The data collection technique used was a measurement technque and the data collection tool used was a wrtten test n the form of multiple choice. Based on data analysis, the average final test of the experimental class was 68. 52 and the average fnal test of the control class was 61.59. The results of the hypothesis test using the polled variance-test obtained tcount of 3.05 while ttable (α = 5%; dk = 23 + 22 - 2 = 43) amounted to 1.681 whch means tcount > ttable, then Ha s accepted. This proves that there s a difference n the final test results of students n the experimental and control classes, n other words, t proves that there s an effect of the application of the mind mapping type cooperative learning model on students' cognitive learning outcomes n thematic learning. Based on the results of the calculation of effect size (d), the result d = 0.92 was obtained, which included high criteria. Thus t can be concluded that the application of the mind mapping type cooperative learning model has a huge influence on students' cognitive learning outcomes n thematic learning n grade V of State Elementary School 84 Sngkawang.